RANCANG BANGUN APLIKASI PENGELOLAAN DATA ALUMNI UNTUK MENDUKUNG ADMINISTRASI AKADEMIK DI POLITEKNIK NEGERI MANADO - Panadjo, Florecita; Mesak, Brayen Gabriel; Waroh, Anthoinete; Pairunan, Toban T.; Kimbal, Anthon A. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study developed a web-based PHP and MySQL application for alumni data management at Politeknik Negeri Manado using the Waterfall method, replacing inefficient manual processes. The application includes admin authentication, alumni data CRUD, search, filter, and automated report generation. SUS evaluation yielded a score of 84.2 ("Very Good"), and Black-Box testing confirmed all functions work as expected. Task completion time decreased by 73.4% compared to manual methods, demonstrating significant improvements in efficiency, accuracy, and organization of alumni data management to support better academic administrative services.